Anti-microbial mechanism of Lonicera japonica and Andrographis paniculata extract in inhibiting Pseudomonas sp. - Wong, Kok Kee; Wong, Rui Rui; Yuka Hara, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Antibiotic resistance reported in Pseudomonas sp. is associated with various opportunistic infections and is a concern in the public health system. The present study investigated the inhibitory effects of ethanol extracts of Lonicera japonica and Andrographis paniculata on Pseudomonas sp. The total phenolic compound (TPC) calculated in gallic acid equivalent (GAE) was 508.6±117.96 mg GAE/100 g dried weight (DW) in L. japonica while A. paniculata contained 129.0 ± 21.00 mg GAE/100 g DW. Both herbs significantly reduced the swarming zone diameters of Pseudomonas sp., even at a concentration as low as 5 mg/mL when compared to the controls. The anti-swarming effect of L. japonica and A. paniculata may be one of the mutual mechanisms underlying their anti-microbial properties. However, only the extract of L. japonica showed cell anti-adhesion activity, which can prevent biofilm formation. Andrographis paniculata extract on the other hand shows the highest activity in disrupting the cell membrane of Pseudomonas sp.